Efficient Synthesis of 4‐Bromo‐N‐(1‐phenylethyl)benzamide, Arylation by Pd(0) Catalyst, Characterization and DFT Study. Issue 29 (1st August 2022) - Raza Shah, Alı; Rasool, Nasır; Bılal, Muhammad; Mubarık, Adeel; Alı Hashmı, Muhammad; Nadeem Akhtar, Muhammad; Imran, Muhammad; Ahmad, Gulraız; Siddiqa, Ayesha; Adnan Alı Shah, Syed
Abstract: The ( S )‐4‐bromo‐ N ‐(1‐phenylethyl)benzamide (3) was synthesized in excellent yield (93 %) by the reaction of 4‐bromobenzoic acid (1) and ( S )‐1‐phenylethanamine (2 ) with the coupling reagent titanium tetrachloride (TiCl4 ). Further, the Pd(0) catalyst was employed to form ( S )‐4‐bromo‐ N ‐(1‐phenylethyl)benzamide analogues (5 a‐i ) by reacting various aryl boronic acids with 4‐bromo‐ N ‐(1‐phenylethyl)benzamide (3 ) in moderate to good yields (62‐89 %). Furthermore, DFT studies were carried out to compute optimized geometries, frontier molecular orbitals, polarizability (α), hyperpolarizability (β), MESP, reactivity descriptors, and NMR spectra. The measured NMR values matched the experimental NMR values well. In this series (5 a‐i ), we predicted that the highest energy difference between the HOMO‐LUMO of compound (5 a) has 4.98 eV, resulting in a more stable compound, and compound (5 g ) has the lowest energy difference between the HOMO‐LUMO 4.63 eV, resulting in the least stable compound. Compound (5h ) has the highest hyperpolarizability (β) value, exhibits a better non‐linear optical (NLO) behaviour compared as compare to other synthesized compounds in the series. Abstract : The reaction of 4‐bromobenzoic acid (1 ) and (S)‐1‐phenylethanamine (2 ) yielded ( S )‐4‐bromo‐ N ‐(1‐phenylethyl)benzamide (3) with an excellent yield (93 %). In the presence of a Pd(0) catalyst, it reacts with various aryl boronic acids to form (S)‐4‐bromo‐N‐(1‐phenylethyl)benzamide analogues (5 a–i). Furthermore, DFT studies were carried out to compute optimized geometries, frontier molecular orbitals, polarizability (α), hyperpolarizability (β), MESP and reactivity descriptors. The Compound (5 h) has the highest hyperpolarizability (β) value and exhibits better non‐linear optical (NLO) behavior when compared to other synthesized compounds.